1012. SENECIO SQUALIDUS: Compositae. (8th March 2022) - Hind, Nicholas; King, Christabel
Summary: The widespread Senecio squalidus L. (Compositae: Senecioneae: Senecioninae), a diploid hybrid species with strong self‐incompatibility, that originated in the British Isles within the last 300 years, is described and illustrated. The origins of this species are briefly outlined. The history of the spread of this plant in the British Isles, and the presence of several natural hybrids is commented on. Senecio squalidus can be separated from other species, and hybrids, by allozyme differences. The species synonymy is thus minimal as it originated in the British Isles. Its morphological recognition encompasses a broader concept within Europe, including the hybrid swarm, between S. aethnensis and S. chrysanthemifolia, on Mount Etna, Sicily, where British material was originally derived. Both narrow concept and broad concept synonymy are provided, including full protologue citations and distribution of type material when known.